KUDA HITAM DARI TIMUR: SEJARAH PERSIPAL 1961-1980 - Syahrul Mubarak, (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2022)
The object of study in this article is the formation and development of Persipal from 1961-1980. The method used in this research is the historical research method. The existence of Palu City football was increasingly significant until finally Persipal was formed and in its development Persipa changed its name to Persipal. Persipal began to enter its heyday between 1974-1979. Persipal's various achievements that year were 1st place in the Interzone Championship in Kolaka, 1st place in the Friendship Tournament in Makassar, 2nd place in PSSI for region IV, breaking into the top 8 of the 1975 PSSI National Championship, penetrating 18 of the 1978 PSSI National Championships, 2nd place in PSSI National Championship/PSSI Division I 1979, Indonesia's representative in the International Tournament in Bangladesh and was dubbed the Dark Horse of the East. In 1980 Persipal began to enter a period of decline after getting a heyday from 1974-1979.